STRATEGY OF DEVELOPMENT FREE SCHOOL BUS SERVICES - Jasman Launtu (International Conference on Social and Islamic Studies, 2021)
Makassar as a metropolitan city, transportation is still a problem, especially public transportation for students. To reduce congestion and minimize the use of private vehicles by students, the Transportation Agency of Makassar City Service provides free school buses for students. This study aims to determine the quality of service and development strategies for free school bus services in Makassar City. Data was collected through observation and questionnaires with simple random sampling technique. The method of analysis used descriptive qualitative analysis and SWOT analysis. The results showed the quality of the free school bus service with variables of tangible (62% in the low category), reliability (54% in the medium category), responses (73% in the high category), assurance (81% in the very high category) and empathy (77% in the high category). Based on the SWOT results, the strategy for developing free school bus services is in quadrant I, namely the rapid growth strategy, by progressively optimizing the strengths and opportunities of free school buses in Makassar City.